SYSTEMATICS AND PARAGENESIS OF URANIUM MINERALS - Finch R.; Murakami T. (My University, 1999)
The oxidation and dissolution of U minerals contributes U to geochemical fluids, both hydrothermal and meteoric. Under reducing conditions, U transport is likely to be measured in fractions of a centimeter, although F and Cl complexes can stabilize U(IV) in solution (Keppler and Wyllie 1990). Where conditions are sufficiently oxidizing to stabilize the uranyl ion, UO22+, and its complexes, U can migrate many kilometers from its source in altered rocks, until changes in solution chemistry lead to precipitation of U minerals. Where oxidized U contacts more reducing conditions, U can be reduced to form uraninite, coffinite, or brannerite. The precipitation of U(VI) minerals can occur in a wide variety of environments, resulting in an impressive variety of uranyl minerals. Because uraninite dissolution can be rapid in oxidizing, aqueous environments, the oxidative dissolution of uraninite caused by weathering commonly leads to the development of a complex array of uranyl minerals in close association with uraninite. Understanding the conditions of U mineral formation and alteration is an important part of understanding the geochemical behavior of U.